Reduced prostacyclin activity in systemic lupus erythematosus. Issue 5 (October 1980) - McVerry, B A; Machin, S J; Parry, H; Goldstone, A H
Abstract : When fresh rabbit aorta is incubated with plasma, prostacyclin, a potent inhibitor of platelet aggregation, is normally released. Plasma obtained from 2 patients with systemic lupus erythematosus (SLE) inhibited prostacyclin activity, while plasma from 22 other patients with SLE and 40 normal control subjects showed normal activity. Absence of prostacyclin activity did not appear to correlate with the clinical severity of the underlying disease. The possible association of this finding and the presence of thrombotic lesions in both patients is discussed.